Impact of mung bean crop market participation on asset accumulation of smallholder households in low-land areas of South Ethiopia - Gata, Girma; Kuma, Berhanu; Tafesse, Alula (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe study aimed at to evaluate the impact of mung bean crop market participation upon asset accumulation of smallholder farmers in lowland areas of South Ethiopia.MethodsAbout 384 smallholder mung bean producer farmers were selected from the lowlands of Wolaita, Gamo and Gofa zones following multistage sampling procedures. The composite asset index development was calculated by multiple correspondence analysis whereas endogenous switching regression was used to evaluate the impact of market participation upon households' asset accumulation.ResultsOut of 384 selected mung bean farmers (74.5%) participated in mung bean markets while 25.5% did not participate in mung bean markets. The estimation result revealed that age of the head of household, numbers of family members, livestock population, perception toward social value, quantity of mung bean product, credit utilization, information accessibility, frequent training on agro-practices, road and market distance from home significantly affected mung bean market participation status. In addition, the asset accumulation of the participants was positively and significantly influenced by age of the head of household, quantity of product and distance from all-weather roads whereas information accessibility negatively affected asset accumulation.DiscussionThe farmers who participated in mung bean markets were more likely (positive) impact on asset accumulation from selling of the product. Therefore, the government and market regulatory bodies should encourage farmers through providing credit facilities, information and frequent training about the new emerging beans and developing other infrastructure facilities to increase the asset accumulation for smoothing elongated shocks in SERS, Ethiopia.